Treatment Results of Geotropic and Apogeotropic Horizontal Canal Benign Paroxysmal Positional Vertigo in a Tertiary Dizziness Clinic - Maas, Britta D. P. J.; van Leeuwen, Roeland B.; Masius-Olthof, Sylvia; van Benthem, Peter Paul G.; Bruintjes, Tjasse D. (Frontiers in neurology, 2021)
Purpose: To determine the effectiveness of our treatment protocol for geotropic and apogeotropic horizontal canal benign paroxysmal positional vertigo (h-BPPV). Methods: We retrospectively evaluated patients with newly diagnosed geotropic and apogeotropic h-BPPV who visited our clinic between July 2017 and December 2019. Patients were treated according to our treatment protocol, which was implemented in 2017. Patients with geotropic h-BPPV were preferably treated with the Gufoni maneuver. In patients with apogeotropic h-BPPV we executed the modified Gufoni maneuver to achieve conversion to the geotropic type. We looked at the number of successful treatments and the number of recurrences within 1 year. Results: We included 102 patients with h-BPPV, 62 (61%) of whom were treated for geotropic h-BPPV. The ratio of apogeotropic to geotropic h-BPPV was 0.65. After the first visit, we observed resolution of horizontal canal BPPV in 71 and 63% of the geotropic and the apogeotropic group, respectively. After the second visit, this percentage increased to 92% for geotropic h-BPPV and 78% for apogeotropic h-BPPV. After 1 year of follow-up we determined a recurrence rate of 32 and 24% for the geotropic and apogeotropic group, respectively. Conclusion: With our treatment protocol we managed to achieve high rates of symptom resolution in the geotropic and apogeotropic type of h-BPPV with acceptable recurrence rates. We observed a relatively high ratio of apogeotropic h-BPPV to geotropic h-BPPV.